2010
DOI: 10.3390/md8072038
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics from Marine Macroalgae for Human and Animal Health Applications

Abstract: The marine environment is an untapped source of bioactive compounds. Specifically, marine macroalgae (seaweeds) are rich in polysaccharides that could potentially be exploited as prebiotic functional ingredients for both human and animal health applications. Prebiotics are non-digestible, selectively fermented compounds that stimulate the growth and/or activity of beneficial gut microbiota which, in turn, confer health benefits on the host. This review will introduce the concept and potential applications of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
206
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(228 citation statements)
references
References 80 publications
(113 reference statements)
2
206
1
3
Order By: Relevance
“…B. coagulans started gaining popularity as a probiotic in recent years due to its ability to form endospores, which are resistant to high heat (a common food processing treatment) and acidity of the stomach. As a result, the These results are consistent with previous studies that showed some pathogenic and commensal E. coli strains could metabolize FOS [36] [37] [38]. Interestingly, while there were no statistically significant differences in ΔOD 600 among the carbohydrate sources for ECN, the ΔOD 600 of non-probiotic E. coli ATCC 33876 was significantly lower in dextrose than in FOS or lactulose (p < 0.0001, Figure 1).…”
Section: Bacterial Growthsupporting
confidence: 82%
“…B. coagulans started gaining popularity as a probiotic in recent years due to its ability to form endospores, which are resistant to high heat (a common food processing treatment) and acidity of the stomach. As a result, the These results are consistent with previous studies that showed some pathogenic and commensal E. coli strains could metabolize FOS [36] [37] [38]. Interestingly, while there were no statistically significant differences in ΔOD 600 among the carbohydrate sources for ECN, the ΔOD 600 of non-probiotic E. coli ATCC 33876 was significantly lower in dextrose than in FOS or lactulose (p < 0.0001, Figure 1).…”
Section: Bacterial Growthsupporting
confidence: 82%
“…HiveAlive™ is HACCP controlled, its ingredients and process are EU approved, and the ingredients are generally regarded as safe (GRAS) establishing a high level of protection for animals and humans. Seaweeds are now routinely used in animal feeds for weight gain and general health, due to their vitamins, minerals, antioxidants, and bio-active compounds (Brownlee, Fairclough, Hall, & Paxman, 2012;Fleurence, 1999;Holdt & Kraan, 2011;Kovač, Simeunović, Babić, Mišan, & Milovanović, 2013;Mayer & Hamann, 2004;Mayer, Rodriguez, Berlinck, & Hamann, 2007;O'Sullivan et al, 2010). Polysaccharide seaweed extracts have recently shown their potential to prevent or control nosema in honey bees (Roussel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Seaweed extracts have the ability to inhibit lipid peroxidation or to scavenge free radicals [29]. In vivo studies have confirmed the antioxidant abilities of seaweed extracts, as well [3,5,6,30], which has suggested their possible uses as phytopharmaceutical and/or nutraceuticals.…”
mentioning
confidence: 82%
“…Epidemiological research has been also suggested their positive effects on human health with an inverse correlation between the incidence of different diseases, related to oxidative stress and the consumption of seaweeds [24]. Others studies have also demonstrated the different therapeutic properties of these marine algae, which were verified in vitro as well as in vivo [3,4,25,26].…”
mentioning
confidence: 91%